VD_FINDINFO HC / 2023 / 315 vom 22. Mai 2023 - VD Tribunal cantonal (2023)
CAS CLAIR, PROCÉDURE SOMMAIRE, EXPULSION DE LOCATAIRE, DROIT D'ÊTRE ENTENDU | 257d CO, 243 al. 2 let. c CPC (CH), 248 CPC (CH), 257 CPC (CH), 69 al. 1 CPC (CH)